O pragmatismo em Kaiser e Ranganathan e o pioneirismo na construção do método analítico-sintético - De Sales, Rodrigo; Guimarães, José Augusto Chaves [UNESP] (My University, 2014)
Considering that Julius Kaiser's Systematic Indexing brought pioneer contributions to the theoretical framework of the subject approach to information, this paper retrieves the foundations of the analiticalsynthetic method conceived by Kaiser which acted as a basis for Ranganathan's faceted theory. In this sense, and by adopting William James' pragmatism as a methodological approach, it analyzes the analitical and sintetic dimensions of Kaiser's indexing method and in what extent they act as a basis for the definition of Ranganathan's method, as well as how both Kaiser's and Raganathan's methods dialogue each other. © 2014 Francisco Javier García Marco y los autores.
Kaiser's and Ranganathan's pragmatism and the peoners of the analytic-sinthetic method
Keywords: Analytical-synthetic methods; Julius Otto Kaiser; S. R. Ranganathan; Subject Approach to information; Systematic indexing